The Bohemian Illustrated Life of Christ. Artistic provenance, iconography and commission of Cod. 485 (Vienna, Austrian National Library) - Studničková, Milada; Horníčková, Kateřina; Theisen, Maria; Theisen, Maria (Artefactum, 2018)
Codex ÖNB 485 is a unique manuscript whose picture cycle is accompanied by short excerpts from the Czech New Testament. The study seeks to present a stylistic, iconographic analysis, and questions possible recipients’ use, considering the manuscript in the context of a moderate Utraquism as was common in Prague around 1440.
Český Život Krista. Provenience, ikonografie a objednavatel kodexu 485 Vídeňské národní knihovny
Keywords: Bohemian book illumination; 15. century; iconography; Utraquism; Codex 485 Vienna Austrian National Library; Český Život Krista; středověké iluminace; ikonografie; 15. století; kodex 485 Vídeňské národní knihovny